Karamzadeh's captivating thoughts and elegant solutions to some popular and classical results revisited: Some comments and explanations - مهرداد نامداری (مدل‌سازی پیشرفته ریاضی)
In this note, we intend to explain and interpret the proofs of some of the classic mathematical results that are made easy by the beautiful mind of Karamzadeh, who has an incredible love for mathematics and has been doing well for years with regards to its popularization in our country.